Macroeconomic determinants of long-term sovereign bond yields in South Africa - Sheunesu Zhou (Cogent Economics & Finance, 2021)
This paper seeks to analyse the impact of government debt and other macroeconomic variables on the long term bond yield for South Africa. Recent increases in the government budget deficit and its corresponding borrowing has renewed interest in understanding fiscal dynamics within the economy. The study employs both the linear and non-linear Auto-regressive distributed lag (ARDL) technique to estimate the determinants of the long-term bond yield. Our results show that the short-term interest rate is the major determinant of the long term yield in both the short-run and long-run. Government debt and the US long term yield positively impact long term bond yields both in the short- and long-run. The rate of inflation, economic growth, nominal effective exchange rate and bank credit all have negative effects on the bond yield in the long-run. Tests for non-linearity reveal that the short-term interest rate has an asymmetric relationship with the long-term bond yield. However, we only establish non-linearity between government debt and bond yields in the long-run. We suggest complementarity between monetary policy and fiscal policy, a systematic program of deleveraging and implementation of structural changes aimed at increasing production.
Keywords: C51; E43; E62; 330; government bond yield; government debt; non-linear ARDL; short-term interest rate